PENGARUH FREE CASH FLOW DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN - Naini, Dwi Ismiwatis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of free cash flow and institutional ownership to the debt policy and influence of free cash flow, institutional ownership, and debt policy to the companyâs value. Aside from using free cash flow and institutional ownership variables as independent variable, this research also uses profitability as control variable. The population in this research is manufacturing companies which are listed in Indonesia Stock Exchange during 2008-2012 periods. The research samples have been selected by using purposive sampling method so the 78 manufacturing companies (338 firm years) have fulfilled the criteria. The analysis technique is the multiple regressions. The result shows that: 1) Free cash flow has positive influence to the debt policy. 2) Institutional ownership has no influence to the debt policy. 3) Profitability has negative influence to the debt policy. 4) Free cash flow has no influence to the companyâs value. 5) Institutional ownership has positive influence to the companyâs value. 6) Debt policy has negative influence to the company value. 7) Profitability has positive influence to the company value.Keywords: Free Cash Flow, Institutional Ownership, Debt Policy, Companyâs Value, and Profitability